Misleading Imaging Findings: Bilateral Mylohyoid Defect Presenting as a Submandibular Mass Due to Sublingual Gland Protrusion - Dagnija Grabovska; Junsiyuan Li; Maija Radziņa; Arturs Balodis (Diagnostics)
Background/Objectives: The muscular base of the oral cavity is formed of the mylohyoid muscle, which forms a sling inferior to the tongue. The muscle is often discontinuous, and defects may include salivary tissues, fat, and/or blood vessels. Hypertrophic sublingual glands located in mylohyoid defects can be herniated into bilateral submandibular spaces and present as palpable masses. The etiology of this condition may be congenital or acquired, and although such anatomical variations are common, they often go unrecognized in clinical practice. Sialoceles are cyst-like structures that result from chronic inflammation or ductal injury, indicating underlying problems with drainage efficiency. Methods: In this case series, we present two patients. Results: The first patient is a 44-year-old female who presented with a slowly enlarging right submandibular mass for two years, while the second is a 70-year-old female who presented with nonspecific neck discomfort, lacking palpable masses. In both, initial imaging (ultrasound and CT) was inconclusive. MRI revealed right sublingual gland herniation through a mylohyoid defect (mylohyoid boutonniere) in both cases. Conclusions: This highlights the importance of comprehensive imaging in the diagnosis of submandibular masses and emphasizes the need for considering mylohyoid boutonniere in cases of bilateral submandibular masses. Further research is warranted into the sialoceles associated with salivary gland abnormalities.